HUBUNGAN PENGGUNAAN KONTRASEPSI SUNTIK DENGAN TEKANAN DARAH DAN BERAT BADAN PADA WANITA USIA SUBUR - Fathiya Luthfil Yumni; Supatmi Supatmi; Sefni Tanti Ferawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: The purpose of this study was to analyze the relationship between injecting contraceptive use and blood pressure and body weight in women of childbearing ageMethods: The design of this research is analytic correlation research using the Croos-sectional method. With a population of 47 injecting family planning acceptors and a sample of 42 respondents using a simple random sampling technique. With the independent variables of injection contraception and the dependent variables of blood pressure and body weight. The instruments used in this study were questionnaires and observation sheets, using the chi-square test.Results: The results of the Chi-Square test between the type of injecting birth control and blood pressure obtained a calculated Chi-Square test value of 6,881 with a significant value of (p = 0.032) there was a significant relationship between the type of injecting birth control and blood pressure. The results of the Chi-Square test between the type of injecting birth control and body weight obtained a calculated Chi-Square test value of 10,521 with a significant value of (p = 0.015), there was a significant relationship between the type of injecting birth control and body weightConclusion:Â The choice of injectable birth control needs to be reconsidered regarding the side effects of use if it is used long term for a later date